2021
DOI: 10.30574/gscarr.2021.7.1.0006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing methods on functional, pasting properties of flours and sensory evaluation of “Amala” made from different yam cultivars

Abstract: The effect of processing methods on the functional, pasting properties of flours and sensory evaluation of “amala” made from three different cultivars of yam were determined using standard analytical methods. The three cultivars of yam namely; Dioscorea caynensis “Amula and Lasinrin) and Dioscorea alata (Cote divoire) were processed using three different methods as following; (a) parboiling with steep water (omi-ogi) in aluminium pot and local clay pot (b) parboiling with clean water in aluminium pot and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
2
3
1
Order By: Relevance
“…The final viscosity of the composite semolina sample was 338.92 RVU. The value obtained is lower compared to the values (2464 -4332 cP) reported by Olarenwaju et al (2021) for semolina produced from different yam cultivars. The difference might be as a result of variations in the product formulation.…”
Section: Pasting Properties Of Semolina Produced From Blends Of Yam O...contrasting
confidence: 77%
See 4 more Smart Citations
“…The final viscosity of the composite semolina sample was 338.92 RVU. The value obtained is lower compared to the values (2464 -4332 cP) reported by Olarenwaju et al (2021) for semolina produced from different yam cultivars. The difference might be as a result of variations in the product formulation.…”
Section: Pasting Properties Of Semolina Produced From Blends Of Yam O...contrasting
confidence: 77%
“…Pasting properties of semolina from blends of 80 % yam, 10 % orange fleshed sweet potato and 10 % beetroot flours.Peak viscosity of the semolina sample was 268.17 RVU. The results obtained in this study fell within the range reported byOlarenwaju et al (2021) who reported values ranging from 1783 -3682 RVU for flours prepared from different yam species; but lower than the values (915 -1789 RVU) reported by…”
supporting
confidence: 83%
See 3 more Smart Citations